Enhancing Photostability of Prochloraz via Designing Natural Acid-Derived Prochloraz-Based Ionic Liquids - Zhiqiang Gao; Fengmao Liu; Qingrong Peng; Wenzhuo Wang (Molecules)
Converting pesticides into ionic liquids by designing counterions can modulate their physicochemical properties, thus improving their efficacy and environmental safety. In this study, eight prochloraz-based ionic liquids (PILs) were synthesized using natural organic acids, and their physicochemical properties, toxicity, antifungal activity, and efficacy in postharvest mango preservation were evaluated. The results showed that the physicochemical properties of propiconazole, including water solubility, logKow, surface activity, and light stability, could be adjusted by selecting counterions with varying structures. These properties were correlated with toxicity to zebrafish embryos and antifungal activity against Colletotrichum gloeosporioides. Notably, except for the benzoate PIL, the photostability of the other seven PILs was enhanced under UV irradiation, with the cinnamate PIL exhibiting a half-life 2.28 times longer than prochloraz. Spectral analysis indicated that the anions influenced photostability by shielding or interacting with the cations. Furthermore, the three selected PILs improved pesticide deposition on the mango surface during preservation, and the salicylate PIL enhanced pesticide penetration into the fruit, potentially contributing to its therapeutic activity. In conclusion, the ionic liquid strategy offers an effective method to modify pesticide properties, improve photostability, reduce losses, and optimize pesticide formulation.